Persepsi Guru dalam Implementasi Kurikulum Merdeka di SMA Negeri 1 Durenan - Ananta Nur Aribyan; Bagus Setiawan (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
This research is motivated by the understanding that the curriculum is one of the crucial elements in the learning process at all levels of education. The Independent Curriculum is expected to serve as an educational program aligned with targeted objectives. This curriculum represents a form of educational reform focused on transforming school culture. It aims to innovate learning by emphasizing student-centered approaches, ultimately aligning graduates with the profile of a Pancasila student. Teachers, as drivers of independent learning, are required to be active, enthusiastic, creative, innovative, and skilled in becoming facilitators for change in schools, thereby creating a supportive learning environment by fostering close relationships with students. The research questions include: (1) How do teachers perceive the Independent Curriculum at SMA Negeri 1 Durenan? (2) What factors influence teachers’ perceptions of the Independent Curriculum? This study employs qualitative research methods and was conducted at SMA Negeri 1 Durenan. Data collection techniques include observation, interviews, and documentation. Data analysis follows Miles and Huberman’s model, which consists of data condensation, data presentation, and conclusion drawing. To test data validity, time triangulation and source triangulation were applied. The study results indicate that teachers perceive the implementation of the Independent Curriculum at SMA Negeri 1 Durenan as strongly supporting the development of Pancasila values in learning, consistent with the national educational goal of shaping students with a Pancasila profile. Additionally, teachers’ perceptions of the curriculum are influenced by their knowledge; teachers require intensive and regular support to facilitate the curriculum’s implementation, need to leverage technology to make learning more interactive, and need to enhance competencies to adapt to changing times. Overall, teachers’ perceptions of the Independent Curriculum are positive.